Utilisation of Youtube Kids Media in Grade IV IPAS Learning - Kurniawan, Rofiq Adi; Sukartono, Sukartono (International Conference on Education for All, 2024)
Information technology advancements are crucial to the field of education because they provide teachers the ability to create innovative teaching methods. Teachers and students can more easily learning using educational media. YouTube Kids is one of the media platforms utilized that are suitable for young viewers. When it comes to teaching science, teachers at Muhammadiyah Elementary School 16 Ka-rangasem have demonstrated that YouTube Kids may be a useful teaching re-source. The purpose of this study is to provide an overview of Muhammadiyah Elementary School 16 Karangasems usage of YouTube Kids video in social sci-ence education. To characterize the phenomena discovered throughout the inves-tigation, this kind of study employs qualitative descriptive research. A case study of YouTube Kids use in Muhammadiyah Elementary School 16 Karangasems Social Natural Sciences curriculum is employed in the research design. The au-thor used observation, documentation, and interviews to gather information. Technical and source triangulation are used to verify the datas veracity after it has been collected. The data analysis techniques employed in this study were reduc-tion, presentation, and conclusion drafting. The studys findings demonstrate that YouTube Kids content can improve children motivation, engagement, and aca-demic performance when it comes to studying social and natural sciences..